Starptautiskā konference "Jauno vēsturnieku zinātniskie lasījumi IX": Konferences referātu tēzes, Valmieras muzejs, 2023. gada 1.–2. decembris - (:unkn) unknown (My University, 2023)
Starptautisko konferenci “Jauno vēsturnieku zinātniskie lasījumi IX” rīko Latvijas Universitātes Latvijas vēstures institūts un Valmieras muzejs, sadarbībā ar Vītauta Dižā Universitāti Kauņā, Lietuvas Vēstures institūtu un Tartu universitātes Vēstures un arheoloģijas institūtu. Starpdisciplinārā konference norisinās devīto gadu, šogad piesaistot 32 jaunos pētniekus, kuri aplūko dažādus vēstures aspektus no aizvēstures līdz mūsdienām. Referātu autori pārstāv Latvijas Universitāti, Daugavpils Universitāti, Latvijas Mākslas akadēmiju, Eksas-Marseļas universitāti, Tallinas Universitāti, Viļņas Universitāti, Zagrebas Universitāti un dažādas atmiņu institūcijas, un valsts iestādes.

“The Scholarly Readings of Young Historians IX” are organised by the Institute of Latvian History of the University of Latvia and Valmiera Museum, in co-operation with Vytautas Magnus University in Kaunas, the Lithuanian History Institute and the Institute of History and Archaeology of Tartu University. The interdisciplinary conference will be held for the ninth year, attracting 32 young researchers who focus on various aspects of history from prehistory to the present day. The authors represent the University of Latvia, the Daugavpils University, the Art Academy of Latvia, the Aix-Marseille University, the Tallinn University, the Vilnius University, the University of Zagreb and various memory and state institutions. The collection of abstracts is prepared within the framework of the University of Latvia project “Letonika, Diaspora and Inter-cultural Communication”, subproject “The territory of Latvia as a contact zone between different cultural spaces, religious, political, social and economic interests from prehistory to the present day”, project No. ZD2015/AZ85.
International Conference “Scholarly Readings of Young Historians IX” : ABSTRACTS, Valmiera Museum, 1st–2nd December 2023
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Jauno laiku vēsture; 20. gadsimta vēsture; Livonian Small Towns; Runenstones and Gravestones; Ethnographic Sledges; Ansis Kaupēns; Apbedījumi un kapulauki; Viduslaiku Livonijas mazpilsētas; Arheoloģija; Etnogrāfija